2014
DOI: 10.1111/jgs.13107
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Status Can Predict Further Lean Body Mass Decline in Older Adults

Abstract: Frailty status was found to be independently associated with subsequent LMI decline in community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 37 publications
6
28
0
Order By: Relevance
“…These findings are consistent with those of recent studies of the risk factors for frailty, which indicates their validity. [18][19][20][21] In contrast, this study also demonstrated for the first time the relationships between frailty and oral function (occlusal force, masseter muscle thickness, ODK rate). Although reports have indicated that oral function and number of present teeth are associated with frailty, these studies used subjective methods to assess the oral cavity (e.g., questionnaires, interviews) or had only small numbers of subjects.…”
Section: Discussionmentioning
confidence: 51%
“…These findings are consistent with those of recent studies of the risk factors for frailty, which indicates their validity. [18][19][20][21] In contrast, this study also demonstrated for the first time the relationships between frailty and oral function (occlusal force, masseter muscle thickness, ODK rate). Although reports have indicated that oral function and number of present teeth are associated with frailty, these studies used subjective methods to assess the oral cavity (e.g., questionnaires, interviews) or had only small numbers of subjects.…”
Section: Discussionmentioning
confidence: 51%
“…With advances in understanding the varying clinical consequences of sarcopenia and frailty associated with individual aging, [20][21][22] the role of functional measures as risk markers for prospective studies or outcome measures for interventional studies has been ever increasing. 23,24 One of the most extensively used measures for these purposes is the SPPB; its outcome validity and sensitivity to clinically meaningful changes have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The important point is that the effectiveness of this intervention was more pronounced in frail older adults. Recent frailty-related studies show that the frailty status is associated with muscle mass decline in older adults, 42 and regular physical activity may mitigate frailty in frail older adults. 43 Thus, it is possible that the intensity of our intervention was appropriate for frail older adults, but was low for nonfrail older adults.…”
Section: Discussionmentioning
confidence: 99%